Un art du quotidien ? A partir de Georges Perec et Vilhelm Hammershøi - Choplin, Hugues (Labyrinth, 2020)
An art of the everyday? Parting from Georges Perec and Vilhelm Hammershøi Contemporary continental philosophy seems to be deeply connected to art, whether it is poetry and literature (from Heidegger to Derrida), painting (Merleau-Ponty, Maldiney) or music (since Bergson). This connection is built upon the primacy of a trial of the invisible, which is very often a trial of the event. The aim of this article is to establish an art of the everyday freed from this contemporary "eventism". We thus examine how the researches of Georges Perec in literature and of Vilhelm Hammershøi in painting meditate on the strangeness of the everyday – its flatness, its silence – which are irreducible to this aesthetic trial as it can be conceptualized by the philosophy of the life of Deleuze-Guattari and by the humanism of Levinas. This research thus beckons towards an art of the common contesting the contemporary primacy of the vital and the (in)human.